Bangkit: Mengungkap Resiliensi Pada Orang Dengan Hiv/Aids - Peri Setiawan (CV. Doki Course and Training, 2026)
HIV (Human Immunodeficiency Virus) remains a global health issue for which there is currently no cure. This virus damages the immune system of those infected, leaving the body unable to fight off other infections. If left untreated, the virus will mutate into a more serious disease, namely AIDS. HIV is a complex problem among teenagers, especially among gay groups, where teenagers experiencing this condition will experience double burdens, stress, depression, and even suicidal thoughts, so good resilience is needed in HIV patients. This study used a qualitative method with a phenomenological approach, collecting data through interviews and then analyzing it using IPA techniques. There were two respondents in this study who were HIV-positive and already resilient. The results of this study show that certain aspects play a major role in an individual's path to resilience, and that social and emotional support also influence a person's resilience process.